PENAKSIRAN BOBOT BADAN BERDASARKAN LINGKAR DADA DAN PANJANG BADAN DOMBA DONGGALA - Amiruddin Malewa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The study was aimed to estimate the body weight of Donggala sheep based on their body length and chest diameter using Lambourne and Schoorl equations.  Survey method was used to select the sheep randomly from east Palu, west Palu, and Biromaru. The research results showed that the correlation value of chest diameter with body weight was higher than that with body length. Additionally, t test values of Lambourne and Schoorl equations were lower than the t-Table. This indicates that the body weight of Donggala sheep resulting from direct weighing and from those two equations was no significantly difference. Therefore this study suggested that Lambourne and Schoorl equations are feasible to use for estimating the body weight of Donggala sheeps.